2014
DOI: 10.2337/dc13-2127
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Brain Functional Connectivity Related to Insulin Resistance in Type 2 Diabetes: A Resting-State fMRI Study

Abstract: OBJECTIVEType 2 diabetes is characterized by insulin resistance, which is involved in the development of Alzheimer disease. This study aims to investigate the relationship between abnormal resting-state brain functional connectivity and insulin resistance in type 2 diabetes. RESEARCH DESIGN AND METHODSA total of 30 patients with type 2 diabetes and 31 healthy well-matched volunteers were prospectively examined. Resting-state brain functional connectivity analysis was used to examine the correlation between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
94
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 40 publications
6
94
0
1
Order By: Relevance
“…However, no study has observed decreased functional activity in the PCC of T1DM patients. Interestingly, prior studies have demonstrated reduced resting-state neural activity in the PCC in T2DM patients [37][38][39]. We speculate that T1DM and T2DM also share neuropathological mechanisms in the PCC region.…”
Section: Discussionmentioning
confidence: 60%
“…However, no study has observed decreased functional activity in the PCC of T1DM patients. Interestingly, prior studies have demonstrated reduced resting-state neural activity in the PCC in T2DM patients [37][38][39]. We speculate that T1DM and T2DM also share neuropathological mechanisms in the PCC region.…”
Section: Discussionmentioning
confidence: 60%
“…Resting-state functional connectivity is also altered in T2DM subjects, and the severity of impairment correlates with the degree of insulin resistance (18,19). The effects of intranasal insulin on resting-state connectivity have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased functional connectivity between the PCC and MTG was previously observed in diabetic patients. [29] Another study also suggested dysfunction in the PCC and MTG, which are the core components of the default mode network. [30] The cortical thickness of the PCC and MTG is also associated with the executive function of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%